Childhood Stroke: Awareness, Interest, and Knowledge Among the Pediatric Community - Bonfert, Michaela V.; Badura, Katharina; Gerstl, Julia; Borggraefe, Ingo; Heinen, Florian; Schroeder, Sebastian; Olivieri, Martin; Weinberger, Raphael; Landgraf, Mirjam N.; Vill, Katharina; Tacke, Moritz; Berweck, Steffen; et al. (Frontiers in Pediatrics, 2018)
Objective Acute childhood stroke is an emergency requiring a high level of awareness among first-line healthcare providers. This survey serves as an indicator of the awareness of, the interest in and knowledge of childhood stroke of German pediatricians. Methods 1697 physicians of pediatric in- and outpatient facilities in Bavaria, Germany, were invited via email to an online-survey about childhood stroke. Results The overall participation rate was 14%. 46% of participants considered a diagnosis of childhood stroke at least once during the past year, and 47% provide care for patients who have suffered childhood stroke. The acronym FAST (Face-Arm-Speech-Time-Test) was correctly cited in 27% of the questionnaires. Most commonly quoted symptoms of childhood stroke were hemiparesis (90%), speech disorder (58%), seizure (44%), headache (40%) and impaired consciousness (33%). Migraine (63%), seizure (39%) and infections of the brain (31%) were most frequently named as stroke mimics. Main diagnostic measures indicated were magnetic resonance imaging (MRI) (96%) and computer tomography (CT) (55%). Main therapeutic strategies were thrombolysis (80%), anticoagulation (41%), neuroprotective measures and thrombectomies (15% each). 39% of participants had taken part in training sessions, 61% studied literature, 37% discussed with colleagues, and 25% performed internet research on childhood stroke. 93% of participants approve skill enhancement, favoring training sessions (80%), publications (43%) and web based offers (35%). Consent for offering a flyer on the topic to caregivers in facilities was given in 49%. Conclusion Childhood stroke constitutes a topic of clinical importance to pediatricians. Participants demonstrate a considerable level of comprehension concerning the subject, but room for improvement remains. A multi-modal approach encompassing an elaborate training program, regular educational publications in professional journals, and web based offers could reach a broad range of health care providers. Paired with a public adult and childhood stroke awareness campaign, these efforts could contribute to optimize the care for children suffering from stroke.